Evaluation of the Quality of Pharmaceutical Services in Private Hospitals in Sukoharjo in 2023 - Fauziah, Nindia Fitra; Yunita Nugraheni, Ambar (P3M Universitas 'Aisyiyah Surakarta, 2024)
Introductory: Minimum Service Standards are very important because they are a benchmark for the performance of health services provided in hospitals. Objective:This study aims to evaluate the quality of pharmaceutical services at the Private Hospitals in Sukoharjo based on indicators of waiting time for ready-made and compounded medicine services, customer satisfaction, and writing prescriptions according to the formulary. Method:This research is non-experimental research with observational research and descriptive analysis..Result:the waiting time indicator for compounded medicines of 31 minutes and non-mixed medicines of 24 minutes meets the Minimum Hospital Service Standard. For the customer satisfaction indicator, the result was 88.8%, and the conformity of prescription writing with the formulary with a result of 83.1% had achieved the target of the National Indicator for Hospital Service Quality based on the Republic of Indonesia Minister of Health Regulation No . 30 of 2022.Conclusion:From the results of this research it can be concluded that the Private Hospitals in Sukoharjo Hospital Pharmacy Installation have met the Minimum Service Standards (SPM) and National Service Quality Indicators that have been determined